Biopesticide for overcoming caterpillar pests on cabbage plant (Brassica oleracea L) - Taufik, Muhammad; Cahyadi, boby; Tarigan, Enita Dewi br; Razali, Mariany (Journal of Saintech Transfer, 2020)
Bukit Rumah Sendi Farmer Group is one of the farmer groups in Ujung Sampun Village, which consists of 22 family heads. Ujung Sampun Village is one of the villages in Dolat Rayat subdistrict, Karo District in Provinsi Sumatera Utara. This partner distance is about 70 km from Universitas Sumatera Utara. Cabbage (Brassica oleracea L) is a commodity planted by this farmer group. Plutella xylostella caterpillars available in cabbage are very much needed from the harvest so they need to be eradicated. Garlic is a crop interrupted by farmers is one of the local commodities besides cabbage. Garlic (Allium sativum) which releases biopesticides can kill caterpillars on cabbage. This activity is to provide innovations about the appropriate technology of biopesticides from raw materials of garlic to eradicate caterpillars as pests of partner cabbage plant diseases. The activities that have been carried out are preparation of garlic as a raw material for biopestides, applying biopesticides to selected community cabbage land every day at 9 am for 30 days. The results show that biopesticides are very effective in killing caterpillar pests with a mortality rate of 95%.